A Avaliação de desempenho empresarial: o passo seguinte à implantação do sistema de gestão - Marçal, Carlos Alberto Meireles (2008)
This study aimed to verify the steps involved in the deployment of Balanced Score Card as a system of strategic management at a Brazilian public company. It also had intended to verify if company can be considered a Strategy Focused Organization, by comparing the results of the management system implementation with the items listed in the literature, which also highlights the ability to obtain maximizing the financial and human resources through the strategic alignment. The results demonstrated that the company has implemented the management system according to the method indicated in the literature and after implementation presented evidence that, although has optimizing points on the alignment process, it can be considered a Strategy Focused Organization.